Dampak Pemberian Beberapa Jenis Mikoriza terhadap Pertumbuhan dan Hasil Tanaman Cabai Rawit (Capsicum frutescens L.) - Anggie Febrisia Putri; Mizan Maulana; Naziratil Husna (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aimed to determine the effect of different types of Arbuscular Mycorrhizal Fungi (AMF) on the growth and yield of bird's eye chili (Capsicum frutescens L.). Chili productivity is often constrained by the low availability of phosphorus (P), highlighting the need for biofertilizers that enhance nutrient uptake efficiency. The study was conducted from April to July 2025 at the Suka Tani Sejahtera Coffee Plantation Business Research Center, Bireuen, Aceh. A non-factorial Randomized Complete Block Design (RCBD) was employed with four treatments and three replications, consisting of a control, Glomus sp., Acaulospora sp., and a combination of Glomus sp. + Acaulospora sp. The observed parameters included plant height, number of leaves, number of fruits, fruit weight, fresh shoot biomass, fresh root biomass, root length, and percentage of AMF root colonization. The results showed that AMF application produced different responses among the observed parameters. AMF application had no significant effect on plant height, number of leaves, or fresh shoot biomass, but significantly affected fruit weight, fresh root biomass, and root length. The Glomus sp. treatment produced the highest fresh root biomass (45 g), whereas Acaulospora sp. resulted in the highest number of fruits (350 fruits) and fruit weight (238.67 g). The combined AMF treatment produced the highest fresh shoot biomass (160.67 g), although it did not exhibit a better synergistic effect than the single-species treatments. The highest root colonization reached 48–50% at an application rate of 15 g per plant. In conclusion, Glomus sp. was more effective in promoting root system development, whereas Acaulospora sp. was more effective in improving the generative yield of bird's eye chili.